2013
DOI: 10.1152/ajpendo.00145.2013
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein decreases exercise endurance through rapamycin-sensitive suppression of muscle mitochondria

Abstract: Mitsuishi M, Miyashita K, Muraki A, Tamaki M, Tanaka K, Itoh H. Dietary protein decreases exercise endurance through rapamycin-sensitive suppression of muscle mitochondria. Am J Physiol Endocrinol Metab 305: E776 -E784, 2013. First published July 23, 2013; doi:10.1152/ajpendo.00145.2013.-Loss of physical performance is linked not only to decreased activity in daily life but also to increased onset of cardiovascular diseases and mortality. A highprotein diet is recommended for aged individuals in order to pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…In a study by Mitchell et al, protein restriction was found to improve levels of oxidative stress and inflammation in mice (46). In the study by Mitsuishi et al, weight and exercise capacity were increased in older adults by a HP dietary intervention (47). These results are consistent with the findings in our study.…”
Section: Comprehensive Quantitative Assessment Of Aging Statussupporting
confidence: 92%
“…In a study by Mitchell et al, protein restriction was found to improve levels of oxidative stress and inflammation in mice (46). In the study by Mitsuishi et al, weight and exercise capacity were increased in older adults by a HP dietary intervention (47). These results are consistent with the findings in our study.…”
Section: Comprehensive Quantitative Assessment Of Aging Statussupporting
confidence: 92%
“…In addition, a balanced intake of energy and protein is important when addressing malnutrition in the elderly. Recent studies have shown that high protein intake can increase skeletal muscle mass and muscle strength, but can also cause functional decline in endurance, mitochondrial function, and glucose tolerance ( 77 ). In order to prevent and address malnutrition, sarcopenia, and frailty, it may be useful to include MCTs, which are easily utilized as energy, along with an appropriate amount of protein intake, considering the specific physiological conditions of the elderly.…”
Section: Various Clinical Application Studiesmentioning
confidence: 99%
“…In mammals, rapamycin is a potent inhibitor of TORC1, and also of TORC2 at high doses or chronic treatments [132]. Rapamycin treatment drastically attenuates the detrimental effects of both high protein and high fat diets in mice [133]. Specifically, in mice a significant decrease in the amount and function of muscle mitochondria was seen following a life-long high-protein diet, which was reverted by chronic treatment with rapamycin [133].…”
Section: Dietary Restriction Mitochondria Aging and Longevity Inmentioning
confidence: 99%
“…Rapamycin treatment drastically attenuates the detrimental effects of both high protein and high fat diets in mice [133]. Specifically, in mice a significant decrease in the amount and function of muscle mitochondria was seen following a life-long high-protein diet, which was reverted by chronic treatment with rapamycin [133]. Inhibition of mTOR by rapamycin also activates selective degradation of unfit mitochondria through mitophagy, a process critical for mitochondrial quality control.…”
Section: Dietary Restriction Mitochondria Aging and Longevity Inmentioning
confidence: 99%